Effect of intraoperative esmolol infusion on anesthetic, analgesic requirements and postoperative nausea-vomitting in a group of laparoscopic cholecystectomy patients - Dereli,Necla (2015)
PURPOSE: Postoperative pain and nausea/vomitting (PNV) are common in laparoscopic cholecystectomy patients. Sympatholytic agents might decrease requirements for intravenous or inhalation anesthetics and opioids. In this study we aimed to analyze effects of esmolol on intraoperative anesthetic-postoperative analgesic requirements, postoperative pain and PNV. METHODS: Sixty patients have been included. Propofol, remifentanil and vecuronium were used for induction. Study groups were as follows; I - Esmolol infusion was added to maintenance anesthetics (propofol and remifentanil), II - Only propofol and remifentanil was used during maintenance, III - Esmolol infusion was added to maintenance anesthetics (desflurane and remifentanil), IV - Only desflurane and remifentanil was used during maintenance. They have been followed up for 24 h for PNV and analgesic requirements. Visual analog scale (VAS) scores for pain was also been evaluated. RESULTS: VAS scores were significantly lowest in group I (p = 0.001-0.028). PNV incidence was significantly lowest in group I (p = 0.026). PNV incidence was also lower in group III compared to group IV (p = 0.032). Analgesic requirements were significantly lower in group I and was lower in group III compared to group IV (p = 0.005). Heart rates were significantly lower in esmolol groups (group I and III) compared to their controls (p = 0.001) however blood pressures were similar in all groups (p = 0.594). Comparison of esmolol groups with controls revealed that there is a significant decrease in anesthetic and opioid requirements (p = 0.024-0.03). CONCLUSION: Using esmolol during anesthetic maintenance significantly decreases anesthetic-analgesic requirements, postoperative pain and PNV.